IMPLEMENTASI PASAL 3 AYAT 1 UNDANG-UNDANG NOMOR 2 TAHUN 1960 TENTANG PERJANJIAN BAGI HASIL DI DESA KINTAMANI KECAMATAN KINTAMANI KABUPATEN BANGLI - I Komang Agus Murdana Yasa; Putu Riski Ananda Kusuma; Supriyanto (Jurnal Ilmu Hukum Sui Generis, 2026)
This study aims to analyze the implementation of Article 3 Paragraph (1) of Law Number 2 of 1960 concerning Sharecropping Agreements in Kintamani Village, Kintamani District, Bangli Regency, and to identify the obstacles affecting its implementation. This research employed an empirical legal research method with a descriptive empirical juridical approach. Primary data were collected through field observations and interviews with the Village Head, traditional community leaders, landowners, and sharecroppers, while secondary data were obtained through a literature review of legislation, books, and scholarly journals. The findings indicate that the implementation of Article 3 Paragraph (1) of Law Number 2 of 1960 has not been effective. A total of 87.5% of respondents still conduct sharecropping agreements orally through the traditional nyakap system, which is based on mutual trust, kinship, and long-standing customary practices, while only 12.5% execute written agreements as required by the law. These findings demonstrate a discrepancy between the applicable legal norms (das sollen) and the actual practices within the community (das sein). The primary obstacles to implementation include the strong legal culture that continues to uphold customary practices, the limited public understanding of the legal requirement to establish written agreements, and the lack of effective dissemination, supervision, and legal guidance from the village government and relevant authorities. The study concludes that improving the effectiveness of Law Number 2 of 1960 requires strengthening public legal awareness, enhancing the government's role in legal education and supervision, and promoting harmony between state law and the living law practiced within the community. Such efforts are essential to ensure legal certainty and legal protection for both landowners and sharecroppers in the implementation of agricultural sharecropping agreements.